HEPES activates a MiT/TFE-dependent lysosomal-autophagic gene network in cultured cells: A call for caution. Issue 3 (4th March 2018) - Tol, Marc J.; van der Lienden, Martijn J.C.; Gabriel, Tanit L.; Hagen, Jacob J.; Scheij, Saskia; Veenendaal, Tineke; Klumperman, Judith; Donker-Koopman, Wilma E.; Verhoeven, Arthur J.; Overkleeft, Hermen; Aerts, Johannes M.; Argmann, Carmen A.; et al.
ABSTRACT: In recent years, the lysosome has emerged as a highly dynamic, transcriptionally regulated organelle that is integral to nutrient-sensing and metabolic rewiring. This is coordinated by a lysosome-to-nucleus signaling nexus in which MTORC1 controls the subcellular distribution of the microphthalmia-transcription factor E (MiT/TFE) family of "master lysosomal regulators". Yet, despite the importance of the lysosome in cellular metabolism, the impact of traditional in vitro culture media on lysosomal dynamics and/or MiT/TFE localization has not been fully appreciated. Here, we identify HEPES, a chemical buffering agent that is broadly applied in cell culture, as a potent inducer of lysosome biogenesis. Supplementation of HEPES to cell growth media is sufficient to decouple the MiT/TFE family members–TFEB, TFE3 and MITF–from regulatory mechanisms that control their cytosolic retention. Increased MiT/TFE nuclear import in turn drives the expression of a global network of lysosomal-autophagic and innate host-immune response genes, altering lysosomal dynamics, proteolytic capacity, autophagic flux, and inflammatory signaling. In addition, siRNA-mediated MiT/TFE knockdown effectively blunted HEPES-induced lysosome biogenesis and gene expression profiles. Mechanistically, we show that MiT/TFE activation in response to HEPES requires its macropinocytic ingestion and aberrant lysosomal storage/pH, but is independent of MTORC1 signaling. Altogether, our data underscore the cautionary use of chemical buffering agents in cell culture media due to their potentially confounding effects on experimental results.